Imagination and representation: cognitive mapping of Merida Historic Centre by students at Yucatan Autonomous University (2012)
The article presents the results of an academic research conducted in Merida, Mexico, in which 130 students attending different schools at Yucatan Autonomous University were asked to do cognitive maps from Merida Historic Centre. Researchers sorted all maps into four different categories and analyzed the marked distinctions towards place perception, the physical/spatial correspondence between maps and reality, the absences and presences of architectural and urban landmarks, the relation between the map and the specific studies in which students are involved in, and the main objects and references included in the maps, as well as their frequency. Researchers conclude that cognitive maps are an appropriate instrument for studying human settlements, since they clearly show how city dwellers perceive and provide meaning to architectural and urban structures in the places they inhabit.